Evaluation of Serum malondialdehyde concentrations and enzymatic activity of paraoxonase and arile esterase in women with a recurrent spontaneous abortion - Sanjadi M (Fiyz̤, 2019)
Background: Recurrent spontaneous abortion (RSA) is considered as a harmful event for couples, and can lead to serious problems such as anxiety and depression in couples. Malondialdehyde (MDA) is involved in a variety of disorders including spontaneous abortion (RSA). Paraoxonase and Ariel Esterase are antioxidant enzymes with various protective effects. This study aimed to investigate the relationship between serum MDA level and enzymatic activity of paraoxonase and arile esterase enzymes with RSA risk. Materials and Methods: In this case-control study, 53 RSA patients and 47 healthy age- and sex-matched subjects as the control group were enrolled in the study. Level of MDA were determined in serum sample by using a calorimetrically method with thiobarbituric acid (TBA). The activity of enzymes Paraoxonase and arylesterase were measured by spectrophotometry. Result: The mean serum level of MDA was significantly increased in RSA patients compared to a healthy control group (5.85±1.00 vs. 5.47±0.77, P<0.05). We did not observe any significant difference between two groups in mean activity of enzymes Paraoxonase and arylesterase. We found a positive statistical correlation between the serum levels of MDA and anti-paternal cytotoxic antibody (APCA) (r=+0.20, P=0.04). Conclusion: The present study reveals that oxidative stress and lipid peroxidation in women with a history of spontaneous abortion may increase and subsequently may play a role in non-pregnant women with a history of RSA. Therefore, the increase of oxidative stress in women with a history of RSA is not related solely to pregnancy.